El trabajo infantil en las bloqueras de Latacunga - Bedón Mena, Andrés David (2016)
The present investigation the educational development of the minors who work in the blockers of the Eloy Alfaro Parish was analyzed. This research has a descriptive character, since it seeks to specify in which situations, characteristics and social contexts the working children of the blockers develop; Are involved 10 families belonging to the area, teachers of the Ana Páez Educational Unit, employees / owners of the blockers and technicians of the Ministry of Economic and Social Inclusion (MIES). The deductive-inductive method was used; The techniques used were questionnaires, surveys and in-depth interviews. It was found that working children developed adult attitudes, since their rights as minors were violated; They could not play or study because of work. The academic level was lower than that of his colleagues who did not work. The MIES and the Board of Protection of Cotopaxi Priority Group, through strategies based on agreements, seek to eradicate the work of minors.